BIOMEDICAL WASTE MANAGEMENT: A QUESTIONNAIRE STUDY ON ASSESSMENT OF KNOWLEDGE, ATTITUDE AND PRACTICES AMONG HEALTH CARE PROFESSIONALS IN ORANGE CITY HOSPITAL & RESEARCH INSTITUTE, NAGPUR. - Ramakrishna Shenoi; JIGNESH RAJGURU; Anup Marar (Journal of Biomedical and Pharmaceutical Research, 2020)
Health care waste is a unique category of waste by the source of generation, the quality of its composition, its hazardous nature and the need for appropriate protection during handling, treatment and disposal. Little knowledge and inappropriate technique of handling of biomedical waste can lead to serious consequences on health of the individual handling the bio-medical waste, the community and environment. Biomedical waste management begins with sequential efforts from the early stage of waste generation, segregation at the source itself, storage at the site, disinfection and transfer to the terminal disposal site safely. A questionnaire study was conducted in a tertiary care hospital in Nagpur, India to assess the current knowledge, attitude and practices regarding Bio-medical waste management